PENGARUH MANAJEMEN WAKTU TERHADAP KINERJA KARYAWAN KANTOR OTORITAS BANDAR UDARA WILAYAH I SOEKARNO-HATTA JAKARTA - Apri Anggara Putra; Teguh Ariebowo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims at partially determining the influence of time management on the work perfomance of airport authority office employees in Soekarno-Hatta International Airport. The research was conducted using a quantitative approach which the data collection technique was administered through questionnaires. This study sampled, as many as 100 respondents as the airport authority office employees Soekarno-Hatta. Based on the conducted survey, the result of T-test with ANOVA analysis on time management for employee’s work efficiency is 2.406 > 1.987 with significant value less than 0.05. These results indicate that time management had a positive although it was not too significantly affecting on employee performance at the Soekarno-Hatta Region I Airport Authority Office. According to the author's analysis, this is because the items presented in the questionnaire do not mention the use of technology since the author assumed that technology development allows workers to do several tasks at once